THE RENEWAL OF BUNGAYA AGREEMENT IN 1984: MANUSCRIPT ANALYSIS OF ADDATUANG SIDENRENG - Amir, Muhammad; Maryam, Andi (Walasuji : Jurnal Sejarah dan Budaya, 2021)
The renewal of Bungaya Agreement in 1984 was one of a guideline in managing the relationship between the Dutch East Indies and several kingdoms in South Sulawesi. This study not only aimed to describe the renewal of the Bungaya Agreement based on the manuscript of Addatuang Sidenreng, but also explained the background and impacts of the agreement toward the the kingdoms being in South Sulawesi. The method used was a qualitative research method in term of descriptive analysis through history and filology approaches. The study result showed that the renewal of Bungaya Agreement not only facilitated the government of the Dutch East Indies in restoring the position and power of its colonial government in South Sulawesi, but also gave it opportunity to interfere the internal affairs of the kingdoms in South Sulawesi. Therefore, the renewal of Bungaya Agreement was very beneficial for the Dutch government and very detrimental for the kingdoms in South Sulawesi, so it became the cause of conflicts between the two parties in its establishment.Â